The critical points in coaching expertise of professional soccer coaches in Japan - Kitamura, K. (7th World Congress on Science and Football (WCSF), 2011, 2011)
The exceptional levels of coaching require certain types of unique experience, such as meeting with a setback, trial and error, and the fruition of their purpose (Salmela, 1994). This study therefore aimed to investigate the impact of the critical points as a key concept of coaching expertise directly from the coaches` experience. Method Six professional soccer coaches served as participants for this study. In-depth, open-ended interviews were conducted with each coach. Interviews raged between 60 to 90 minutes. The interviews were systematically transcribed verbatim from audio tapes immediately after the completion of each interview, and total of 549 meaning units were extracted from the data set. The data was decontextualized using an inductive procedure for analyzing unstructured qualitative data. Results & Discussion The inductive analysis process resulted in regrouping these interview transcripts into three categories (Fig.1). This study found significant agreement between the perceptions of the concepts on how coaches evaluated their coaching activities in relation to performance enhancement of players and how this support affected their development of coaching excellence. Conclusion The strong relationship between recognition of self-change, refinement of coaching skill, and cultivation of players` mind indicates that coaches direct themselves to commit to deliberate practice of coaching as a way of constructing the coaching mental model.